2014
DOI: 10.2478/aopf-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between juvenile narrow-claw crayfish, Astacus leptodactylus (Eschscholtz), and common water frog, Rana esculenta (L.), tadpoles or common blue damselfly, Enallagma cyathigerum (Charpentier), larvae during rearing under controlled conditions

Abstract: Interaction between juvenile narrow-claw crayfish, Astacus leptodactylus (Eschscholtz), and common water frog, Rana esculenta (L.), tadpoles or common blue damselfly, Enallagma cyathigerum (Charpentier), larvae during rearing under controlled conditions Dariusz Ulikowski, Iwona Piotrowska, £ucjan Chybowski, Tadeusz Krzywosz, Piotr Traczuk Received -07 July 2014/Accepted -06 October 2014. Published online: 31 December 2014 ©Inland Fisheries Institute in Olsztyn, Poland Citation: Ulikowski D., Piotrowska I., C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In our study, the survival of juvenile A. leptodactylus was highest in the group where the crayfish were kept separately in individual compartments. This is another confirmation of previous results that this is the only way to completely eliminate crayfish cannibalism (Ulikowski et al., ). Cannibalism is one of the main reasons for the decline in survival of juvenile A. leptodactylus during their rearing, and survival decreases with increasing holding density (Ulikowski & Krzywosz, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, the survival of juvenile A. leptodactylus was highest in the group where the crayfish were kept separately in individual compartments. This is another confirmation of previous results that this is the only way to completely eliminate crayfish cannibalism (Ulikowski et al., ). Cannibalism is one of the main reasons for the decline in survival of juvenile A. leptodactylus during their rearing, and survival decreases with increasing holding density (Ulikowski & Krzywosz, ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study showed that the presence of N. glauca caused a reduction in activity of juvenile A. leptodactylus . A similar effect was observed in the case of the impact of predatory fish on crayfish (Appelberg, Söderbäck & Odelström, ), as well as in case of the impact of dragonfly larvae or frog tadpoles on juvenile crayfish (Ulikowski et al., ). By changing their behaviour, crayfish can survive in environments with a high density of potential predators.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations